HASIL BELAJAR PESERTA DIDIK TENTANG KERAGAMAN BUDAYA DI INDONESIA MENGGUNAKAN MODEL QUANTUM LEARNING PADA KELAS IV SD NEGERI 118 PALEMBANG - Rika Wiani; Siti Dewi Maharani; Rudi Susanto (Jurnal Inovasi Sekolah Dasar, 2021)
AbstractThe study airned to through the Quantum Learning model it can improve student the result of learning about cultural diversity in Indonesia four grade of SDN 118 Palembang. The subjects were 24 students from the A class of four grade students consisted of 10 boys and 14 girls. This research uses Classroom Action Research (CAR) by 3 cycles. From the results of this study there was an increase in student result of learning with the minimum completeness criteria (KKM) 65, in the first cycle there were 13 students who completed learning or the percentage of learning completeness was 54.16%, while the second cycle had an increase, there were 16 students who completed learning or the percentage of learning completeness was 66.6% and in cycle III there were 21 students who had finished learning or the percentage of learning completeness was 87.5% so that they had reached classical completeness, the refore this study was declared successful. So it can be concluded that through the application of the Quantum Learning model can improve student the result of learning about cultural diversity in Indonesia four grade of  SD Negeri 118 Palembang. Keyword: Quantum Learning model, the result of learning, cultural diversity in Indonesia. AbstrakTujuan penelitian  ini adalah melalui model Quantum Learning dapat meningkatkan hasil belajar peserta didik tentang keragaman budaya di Indonesia pada kelas IV SDN 118 Palembang. Subjek penelitian adalah peserta didik kelas IV A yang berjumlah 24 terdiri 10 laki-laki dan 14 perempuan. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan 3 siklus tindakan. Dari hasil penelitian ini terjadinya peningkatan hasil belajar peserta didik dengan kriteria ketuntasan minimum (KKM) 65, siklus I ada 13 peserta didik yang tuntas belajar atau persentase ketuntasan belajar sebesar 54,16%, Sedangkan siklus II mengalami peningkatan, ada 16 peserta didik yang tuntas belajar atau persentase ketuntasan belajar sebesar 66,6 % dan pada siklus III terdapat 21 peserta didik yang tuntas belajar atau persentase ketuntasan belajar sebesar 87,5%  sehingga telah mencapai ketuntasan klasikal oleh karena itu penelitian ini dinyatakan berhasil. Jadi dapat disimpulkan bahwa melalui penerapan model Quantum Learning dapat meningkatkan hasil belajar peserta didik tentang keragaman budaya di Indonesia pada kelas IV SD Negeri 118 Palembang. Kata kunci : Model Quantum Learning, Hasil Belajar Peserta Didik, Keragaman Budaya di          Indonesia.